Visceral adiposity in patients with psoriatic arthritis and psoriasis alone and its relationship with metabolic and cardiovascular risk. (24th November 2020) - Toussirot, Eric; Aubin, François; Desmarets, Maxime; Wendling, Daniel; Augé, Benoit; Gillard, Jérome; Messica, Olivier; Guillot, Xavier; Laheurte, Caroline; Monnet, Elisabeth; Dumoulin, Gilles
Abstract: Background: Fat mass distribution, especially in the abdominal visceral region, has been rarely evaluated in patients with PsA or psoriasis (PsO). Methods: Patients with PsA and patients with PsO alone were evaluated and compared with control subjects (1:1 ratio in each patient group) matched for age, sex and BMI category. Body composition and fat distribution (android and visceral fat) were evaluated by DXA. Anthropometric measurements, disease activity and the systematic coronary risk evaluation (SCORE) cardiovascular risk were assessed. Metabolic parameters (insulin, homeostasis model assessment for insulin resistance), serum adipokines [total and high-molecular-weight adiponectin, leptin, resistin and retinol-binding protein-4 (RBP4)] were measured. Results: Data for 52 patients with PsA and 52 patients with PsO and their respective paired controls were analysed. Android fat and visceral fat were found to be significantly higher in patients with PsO compared with their controls, while these measurements did not differ between patients with PsA and their controls. By multivariate analysis, after adjusting for age, sex and BMI, visceral fat was higher in PsO patients compared with PsA patients ( P = 0.0004) and the whole group of controls ( P = 0.0013). Insulin levels and HOMA-IR were increased in both PsA and PsO groups. High-molecular-weight/total adiponectin ratio was decreased in patients with PsO. RBP4 was significantly higher in both PsA and PsO patients. In patients with PsO, visceral fat strongly correlated with SCORE ( r  = 0.61). Conclusion: Visceral fat accumulates more in PsO alone than in PsA. Visceral adiposity may be a more pressing concern in PsO relative to PsA. Trial registration: The ADIPSO study (Évaluation du tissu ADI peux et des adipokines dans le PSO riasis et le rhumatisme psoriasique et analyse de ses relations avec le risque cardiovasculaire) is a case–control study conducted in Besançon, France, and is registered on ClinicalTrials.gov under the number NCT02849795.